Analisis Keamanan Jaringan dan Perlindungan Data Terhadap Serangan Siber di Perusahaan Luar Sekolah - Muhammad Mikail Ziyad; Suprih Widodo (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Threats to vital objects and file security are growing rapidly. Cybercriminals are becoming more cunning and skilled at exploiting security vulnerabilities in digital systems. To improve cybersecurity, a thorough analysis of the threats faced in the digital environment and applicable solutions is required. The aim of this research is to analyze vital objects, identify the main challenges in protecting them from cyber attacks on personal data in Out-of-School companies. The research method uses a qualitative approach using interview and observation techniques. Potential cybercrime threats in Indonesia include hacking, cracking, cyber sabotage and spyware. The risk management process involves identifying, assessing, addressing and controlling risks. To anticipate these threats, technological experts are needed to support the development of advanced national defense systems and establish a cyber security command center.